PENGEMBANGAN KREATIVITAS GURU SERTA MERANGSANG KREATIVITAS ANAK USIA DINI - Fitriani, Laily; Harjanty, Rokyal (LPPM Institut Pendidikan Nusantara Global, 2022)
The development of a child's creativity should start from a creative teacher, because basically early childhood is a very decisive period for a child's adult life. Therefore we need teachers who are able to develop children's creativity. In this research, the goal was to make educators aware of the importance of developing a child's creativity and be able to develop their creativity. This research used a type of literature study research.